Complex Assessment and Justification of the Quality Indicators of Gases Obtained Based on Recycled Fibers (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
in this article, the complex evaluates the physical and mechanical properties of fabrics obtained from a mixture of different compositions and recycled fibers at the joint venture of Safira-Samira Textile LLC, EURASIYA ALLIANCE TEX LLC in the Bukhara region and CHACH TEX LLC in the Chirchik district of Tashkent area and recommended the best option.